Biology and Control of Sorghum-almum in Sugarcane - Dennis Calvin Odero; Ron Rice; Les Baucum (EDIS, 2013)
Sorghum-almum is a weak, perennial rhizomatous grass. Leaves of seedlings are rolled in a bud with a fringed membranous ligule. Seedlings often resemble corn seedlings when small. Stems of mature plants are stout and erect, reaching up to 14 feet tall. Leaf blades are flat and sandpapery. Sorghum-almum is commonly found in the southern part of Florida in sugarcane fields and along ditches, canals, and roadsides. This 3-page fact sheet was written by Dennis Calvin Odero, Ron Rice, and Les Baucum, and published by the UF Department of Agronomy, January 2013.